(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the legal mechanisms for implementing scientific research in public-private partnerships. The regulatory and legal framework of PPPs, contractual regulation, intellectual property rights, risk sharing, monitoring, and accountability institutions are considered from a scientific perspective.